Laço, ritual, máscara e mimese: um olhar para o brincar sob a ótica da compreensão - Rodrigues Iuama, Tadeu (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This essay takes a stroll through the fields of playing, communicating and their relations. Thus, beginning with the etymology of the verb to play, we identify the adherence between this action and communication such as it is understood in the Centro Interdisciplinar de Semiótica da Cultura e da Mídia (Cisc), a research group linked to the Graduate Program in Communication and Semiotics of the Catholic University of São Paulo (PUC-SP). We connect religion and communication based on Miklos, religion and ritual based on Eliade and ritual and game based in Huizinga. Then, we expand the scope of our subject based on Caillois by drawing attention to the concept of mimesis in both Gebauer and Wulf simultaneously. Our main idea is that the act of playing may be circumscribed in a comprehensive manner by applying different theoretical points of view from different fields of knowledge, thus attempting to embrace new horizons for comprehension as a method.